Fibroblast Growth Factor 2-engaged cell spheroid for stem cell therapy: role of Interleukin 8 in the immune-modulatory effectiveness in the critical limb ischemia model - Kim, Eunyeong; Joo, Yunji; Kim, Jong-Wan; Kim, Sang-Heon (Oxford University Press, 2025)
BACKGROUND Stem cell therapy has emerged as a promising approach for treating critical limb ischemia (CLI), a condition caused by atherosclerosis that results in reduced blood flow and limb necrosis. However, the underlying therapeutic mechanisms involving factors secreted from stem cells are still in the early stages of exploration. This study focuses on investigating the tissue regenerative effects of interleukin-8 (IL8) secreted from cell spheroids. METHODS Human adipose-derived stem cells (hASCs) were cultured on FGF2-tethered surfaces to form spheroid (FECS-Ad). A murine CLI model was established through femoral artery dissection, followed by the injection of various treatments, including PBS, hASC, FECS-Ad, IL8-silenced FECS-Ad, and recombinant IL8. RESULTS Comparative analyses revealed that FECS-Ad injection resulted in a higher percentage of salvaged limbs, but these effects were attenuated when IL8 was silenced in FECS-Ad. Immunofluorescence staining, flow cytometry analysis and RT-qPCR of M1 and M2 macrophage markers demonstrated that IL8 has the ability to polarize macrophages to M2 type. Notably, FECS-Ad injection reduced apoptotic markers (caspase 8 and TUNEL) in ischemic tissues, whereas IL8 knockdown in FECS-Ad increased the proportion of apoptotic cells. FECS-Ad injected tissues showed larger regenerating muscle fibers with centrally located nuclei. Knockdown of IL8 in FECS-Ad decreased the area and size of regenerating muscle fibers. CONCLUSIONS Our findings underscore the dual role of IL8 in safeguarding muscle tissues from degeneration and orchestrating immunomodulatory effects by finely tuning tissue inflammation and macrophage polarization. This study highlights IL8 as a pivotal paracrine factor contributing to tissue regeneration in the context of stem cell therapy for CLI.